Information security improving for substandard shipping - Вільський, Геннадій Борисович; Бень, Андрій Павлович (Ukrainian Scientific Journal of Information Security, 2015)
Seagoing vessels with operational inconsistencies complex are characterizing substandard shipping and pose a real threat to the navigation security and the aquatic environment. The lack of science-based research methodology of the formation, maintenance and circulation navigation content, assessment of the vessel, as the object information security is reflected in the management of shipping in general and hinders its content. Maritime information security is an actual scientific task. In this paper, authors identified the major risks and formalized substandard shipping associated with information security vehicles. Main scientific content of this paper are presented in the form of technical provisions on automated decision support system for vessel traffic control posts. An estimate performance criterion optimal effectiveness of the proposed system was showed.